If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 2 = 29x + -2 Reorder the terms: 2 + 9x = 29x + -2 Reorder the terms: 2 + 9x = -2 + 29x Solving 2 + 9x = -2 + 29x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-29x' to each side of the equation. 2 + 9x + -29x = -2 + 29x + -29x Combine like terms: 9x + -29x = -20x 2 + -20x = -2 + 29x + -29x Combine like terms: 29x + -29x = 0 2 + -20x = -2 + 0 2 + -20x = -2 Add '-2' to each side of the equation. 2 + -2 + -20x = -2 + -2 Combine like terms: 2 + -2 = 0 0 + -20x = -2 + -2 -20x = -2 + -2 Combine like terms: -2 + -2 = -4 -20x = -4 Divide each side by '-20'. x = 0.2 Simplifying x = 0.2
| 4(x-5)=7-17 | | 23-6x=-9x | | 7+5x+2x=42 | | 24x=13x-5 | | -20.3=6w+3 | | 8k+2=36k | | q/8/3 | | J/5-8=4 | | 2x+6+6x=30 | | 7(p-3)=4 | | 3/3/-1/3 | | u/4=52 | | 7a+44=-5 | | 3/4n-18 | | 4(x+8)-4=-2 | | 3n-1=-25 | | 6y+10=4 | | h=h/2(3.1416) | | 3m-9+2m=21 | | -9x-54=-9x+108 | | 33113+600t=35000 | | -182/3j | | 3(2y+2)=4(y+7) | | x+64=x+138 | | 6x+4=8x+18 | | X+11+3x-25=180 | | 3/4x=25-4 | | 6x+4=20x+4 | | G(m)=M^4-2m^3+8m-16 | | 8x+18=20x+4 | | 6(y-1)=5y+3 | | -5z-5=-2z+10 |